IMPLEMENTASI KEBIJAKAN PENYUSUNAN STANDAR OPERASIONAL PROSEDUR (SOP) DI LINGKUNGAN PEMERINTAH PROVINSI SULAWESI TENGAH - Yuswadi, Yuswadi (Katalogis, 2015)
This research aims at determining how the implementation of Standard Operational Procedure of government administration in provincial government, Central Sulawesi. Standard Operational Procedure of Governmental Administration is a set of written instructions posted on the organization of the local government tasks. In analyzing the policy, the researcher carried out an implementation theory of Charles O’Jones model approach, which in the theory, a success of policy implementation is determined by three aspects: 1) aspect of the organization; 2) aspect of interpretation (understanding); and 3) aspect of application. This research is a study with qualitative descriptive method. The techniques of the data collections are interviews, observations and documentations. Data sources were obtained from informants considered to know the problems and objectives of this study. This research was located at Regional Secretariat Organization Bureau of Central Sulawesi, Provincial Health Department of Central Sulawesi Office and the Department of Labor and Transmigration of Central Sulawesi. The research was carried out for 3 (three) months since February until April 2015. The result shows that the implementation of Standard Operational Procedure of government administration in provincial government has not run well. The aspect of organization: resources have not been entirely adequate. The aspect of interpretation (understanding): the level of understanding is still lacking due to lack of socialization. Aspect of application: the progress was running slowly due to lack of commitment and control.